Opinion: Imaging Follow-Up after Coiling of Intracranial Aneurysms - van Rooij, W.J.; Sluzewski, M. (American Journal of Neuroradiology, 2009)
SUMMARY: Coiling is increasingly used as treatment for intracranial aneurysms with favorable short-term outcome. Concern exists about long-term reopening and the inherent risk of recurrent subarachnoid hemorrhage (SAH), and long-term imaging follow-up is advocated. It is unknown for how long and how often coiled aneurysms need to be followed and what subgroups carry a higher or lower risk for reopening. Recently, new data have become available that concern the designation of an optimal long-term follow-up protocol. Three studies focused on a special subgroup, the coiled aneurysms that are adequately occluded at 6 months. This subgroup comprises about 80% of all coiled aneurysms. In these aneurysms, the risk of reopening that needs retreatment during the next 5–10 years is very low. In addition, the risk of recurrent SAH is almost zero, even lower than that after clipping. Within the first 5 years after coiling, the incidence of the development of de novo aneurysms or enlargement of existing untreated aneurysms is low, with an extremely low risk of recurrent SAH from these aneurysms. These data suggest that aneurysms that are adequately occluded at 6 months after coiling, in general, do not need prolonged imaging follow-up in the next 5–10 years. More data are needed to identify possible subgroups with adequately occluded coiled aneurysms at 6 months that behave differently on longer follow-up, such as giant aneurysms, partially thrombosed aneurysms, or patients with a positive family history.